Climate change and food systems interactions: Ensuring resilient and healthy diets - Jessica Fanzo; Alison Rose (Field Actions Science Reports)
Food and the systems in which food is produced, processed, packaged, transported, sold, and consumed are becoming increasingly fragile with the changing climate. At the same time, how we grow food, what food we grow, and the trading and selling of these foods have profound consequences on the climate and environment. The world has benefited from technological advances in food systems, but we now stand at our breaking point. Malnutrition is worsening – both hunger and obesity are rising. Much of that malnutrition has to do with the types of diets we consume, which have contributed to adverse health outcomes. We must change the way we govern, manage, and engage with food systems if we want them to produce healthy diets that benefit everyone’s health and nutrition. We need various solutions to do this, and food and climate communities must come together around common goals and actions.